Terra Sem Mal: uma análise da cosmovisão Guarani frente aos impactos da colonização e os desafios contemporâneos - Cotta, Valdirene Aparecida (2024)
This thesis investigates the influence of the myth of the Land Without Evil on the Guarani cosmovision of the Avá-Guarani who lives in the Ocoy Indigenous Land, considering the answers obtained from interviews with individuals belonging to this ethnic group and describing and analyzing the discourse of these participants regarding their cultural practices and their social, spiritual and environmental interactions. The main objective is to record and analyze the influence of the myth of the Land Without Evil as an element that acts as a source of inspiration and resistance in the face of territorial, socioeconomic, spiritual and educational issues. The research is part of a qualitative approach of descriptive nature, theoretically based on studies from different domains of knowledge, including the contributions of Lugon (1977), Melià (1982, 1988, 1990, 2013), Métraux, (1979), Nimuendajú (1987), Schaden (1947), Quijano (2005, 1992), Walsh (2009a, 2009b, 2019), Eliad (1972), Gusdorf (1980) and Bakhtin (1998, 2011). The corpus consists of responses obtained from interviews conducted with a group of people from the ethnic group Avá-Guarani. The results show that the myth continues having vital importance for the community, and can be perceived during daily actions and in the cosmovision of the group. This can be observed in the interviewees' discourse, which revealed the determination and persistence of these individuals in relation to the struggle for territorial justice and in the way they think about the economy, religion and education, formulating reflections on ancestral values and current conflicts. Our results indicate that the myth acts as a reference for principles, norms and values that support social and cultural practices, as well as strategies for action, resistance and the seek for cultural recognition and rights.